Unmet dental health care needs in Serbia - Todorovic, Jovana; Popovic, Natasa; Piperac, Pavle; Djurdjevic Todorovic, Slavica; Terzic Supic , Zorica (Srpski medicinski časopis Lekarske komore, 2021)
Objectives: The study aims were to analyze the socio-demographic, socio-economic, health status characteristics of the population with unmet dental health care needs. Methods: The cross-sectional study included 20069 respondents from the Survey on Income and Living Conditions in the Republic of Serbia in 2014. Multivariate analysis with the self-perceived unmet dental health care needs as an outcome variable was conducted. Results: Nearly every sixth citizen (16.1%) reported unmet dental health care needs. Participants between the ages of 27 and 44 (OR: 1.48, 95% CI: 1.21-1.82), and 45 and 64 (OR: 1.49, 95% CI: 1.19-1.86), participants who assessed their health status as good (OR: 1.91, 95% CI: 1.63-2.25), fair (OR: 3.16, 95% CI: 2.64-3.77), bad (OR: 3.65, 95% CI: 2.94-4.53) or very bad (OR:4.22, 95% CI: 3.10-5.74) had higher likelihood to report unmet dental health need. The most frequent reasons for unmet dental care needs were financial obstacles to the accessibility of dental health care (66.6%), and fear or treatment (15.1%). Conclusions: The study found inequalities in self-perceived unmet dental health care needs according to socio-demographic, socio-economic, health status characteristics of the population. Health policy should adopt a multidimensional approach and eliminate barriers which restrict the accessibility of dental health care.